Preparation and performance of homogenous braids-reinforced poly (p-phenylene terephthamide) hollow fiber membranes - Wang Chun; Yan Dinghe; Song Shubin; Yan Jingjing; Xue Haolong; Xiao Changfa (e-Polymers, 2023)
A novel homogenous braid-reinforced (HBR) poly (p-phenylene terephthamide) (PPTA) hollow fiber membrane was prepared in this study. The effects of PPTA concentration on the morphologies and properties of the membranes were further investigated. The results showed that when the PPTA concentration was 2.0 wt%, the cross-sectional morphology of satisfactory interfacial bonding was achieved and the permeation was still maintained at about 200 (L·m−2·h−1) after ultrasonic vibration. In addition, the tensile force exceeded 600 N, which indicated that the homogeneous effect effectively improved the poor mechanical properties and interfacial bonding. In addition, the HBR PPTA hollow fiber membranes were applied to simulate the membrane bioreactor system to explore the control factors of membrane fouling. The results demonstrated that the average removal of total phosphorus and NH4 +–N was above 49% and 96%, respectively; meanwhile, the operating time was up to 120 days. Furthermore, it was easier to nearly remove the pollutants by chemical cleaning.